Glancing and Then Looking: On the Role of Body, Affect, and Meaning in Cognitive Control - Su, Li; Bowman, Howard; Barnard, Philip (Frontiers in Psychology, 2011)
In humans, there is a trade-off between the need to respond optimally according to the salience level of environmental stimuli and the need to meet our long-term goals. This implies that a system of salience sensitive control exists, which trades task directed processing off against monitoring and responding to potentially high salience stimuli that are irrelevant to the current task. Much cognitive control research has attempted to understand these mechanisms using non-affective stimuli. However, recent research has emphasised the importance of emotions, which are a major factor in the prioritisation of competing stimuli and in directing the allocation of attention. While relatively mature theories of cognitive control exist in the non-affective setting, exactly how emotions modulate cognitive processes is less well understood. The Attentional Blink (AB) task is a useful experimental paradigm to reveal the dynamics of both cognitive and affective control in humans. Hence, we have developed the glance-look model, which has replicated a broad profile of data on the semantic AB task and characterized how attentional deployment is modulated by emotion. Taking inspiration from Barnard’s Interacting Cognitive Subsystems, the model relies on a distinction between two levels of meaning: implicational and propositional, which are supported by two corresponding mental subsystems: the glance and the look respectively. In our model, these two subsystems reflect the central engine of cognitive control and executive function. In particular, the interaction within the central engine dynamically establishes a task filter for salient stimuli using a neuro-biologically inspired learning mechanism. In addition, the somatic contribution of emotional effects is modelled by a body-state subsystem. We argue that stimulus-driven interaction among these three subsystems governs the movement of control between them. The model also predicts attenuation effects and fringe awareness during AB.